3D Printing Adjustable Stiffness External Fixator for Mechanically Stimulated Healing of Tibial Fractures. (23rd December 2021) - Li, Hongwei; Li, Dichen; Qiao, Feng; Tang, Lei; Han, Qi
Abstract : External fixation is a long-standing but well-established method, which has been widely used for the treatment of fractures. To obtain the maximum benefit from the mechanical stimulus, the stiffness of the external fixator should be adjusted properly throughout the treatment phase. Nevertheless, the lack of a valid dynamic adjustable fixation device impedes this possibility. Based on the stiffness adjustment tolerance of the healing callus, this paper proposes an active-dynamic stiffness adjustable external fixator design method to meet stiffness requirements at different stages of the tibial fracture healing process. A novel external fixator with an adjustable stiffness configuration was designed, and the finite element method was used to simulate the stress distribution between fixator and fracture gap. The stiffness adjustment tolerance was determined based on previous studies. According to this tolerance, the optimal block structure dismantling sequence was sought and the corresponding stiffness was calculated through topology optimization for the entire external fixator model. The appropriate amount of variable stiffness at the fracture gap was applied by dismantling the configuration of the block structure external fixator during the healing process. A novel patient-specific adjustable stiffness external fixator for mechanically stimulated tibial fracture reduction and therapy was proposed. This enables surgeons to tailor the construction of the external fixator frame to the clinical needs of each patient. The presented dismantling approach of the block structure to produce conformable stiffness provides a new clinical treatment strategy for tibial fractures.